74.2k views
16 votes
The sum of the reciprocals of 3 - x and 1 - 2x is 6 times the reciprocal of 3 - 4x. Find the value of x.

User Bkqc
by
4.9k points

1 Answer

7 votes

Answer:
(6)/(17)

Explanation:

Reciprocal of
3-x\ \text{is}\ (1)/(3-x)

Reciprocal of
1-2x\ \text{is}\ (1)/(1-2x)

According to question


\Rightarrow (1)/(3-x)+(1)/(1-2x)=6* (1)/(3-4x)\\\\\Rightarrow ((1-2x)+(3-x))/((1-2x)(3-x))=(6)/(3-4x)\\\\\Rightarrow (4-3x)/((1-2x)(3-x))=(6)/(3-4x)


\Rightarrow (4-3x)(3-4x)=6(1-2x)(3-x)\\\Rightarrow 12-16x-9x+12x^2=18-6x-36x+12x^2\\\Rightarrow 12x^2-25x+12=18-42x+12x^2=0\\\Rightarrow 42x-25x=6\\\Rightarrow 17x=6\\\Rightarrow x=(6)/(17)

User Andrew Orsich
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.